Glass Fiber Reinforced Concrete & Its Properties Shrikant Harle, Prof. Ram Meghe (International Journal of Engineering and Computer Science, 2013)
Glass fiber reinforced concrete (GFRC) is a recent introduction in the field of civil engineering. So, it has been extensively used in many countries since its introduction two decades ago. This product has advantage of being light weight and thereby reducing the overall cost of construction, ultimately bringing economy in construction. Steel reinforcement corrosion and structural deterioration in reinforced concrete structures are common and prompted many researchers to seek alternative materials and rehabilitation techniques. So, researchers all over the world are attempting to develop high performance concrete using glass fibers and other admixtures in the concrete up to certain extent. In the view of global sustainable scenario, it is imperative that fibers like glass, carbon, aramid and poly-propylene provide very wide improvements in tensile strength, fatigue characteristics, durability, shrinkage characteristics, impact, cavitations, erosion resistance and serviceability of concrete. The present work is only an accumulation of information about GFRC and the research work which is already carried out by other researchers.